IN VITRO INHIBITION OF CELERY (Apium graveolens L.) EXTRACT ON THE ACTIVITY OF XANTHINE OXIDASE AND DETERMINATION OF ITS ACTIVE COMPOUND - Dyah Iswantini; Tuti Hayati Ramdhani; Latifah K Darusman (Indonesian Journal of Chemistry, 2012)
The objective of this study was to determine the inhibition effect of celery extracts toward xanthine oxidase by in vitro method, and its active compounds. Roots and herb of celery were extracted using water and ethanol solvents. Results indicated that the herbal ethanol extract had the highest inhibition effect (91.40%) at 1400 ppm. The components contained in the herbal ethanol extract were then separated by column chromatography using the best eluent (chloroform : ethyl acetate at 7:3). All of the fractions had inhibition effect greater than 50%. The fraction number 4 was the one with the highest inhibition effect followed by fraction 5 with inhibition percentage of both fractions at 200 ppm were 88.62 and 85.44%, respectively. The analysis of the ultraviolet spectrum of fraction 4 showed the presence of π-π* transition which was resulted by the aromatic C=C, -OH, and C-O chromophores, and also showing the n-σ* transition which was given by -C=O chromophore. The infrared spectrum analysis indicated the presence of aromatic -C=C, -OH, and C=O functional groups. Based on the phytochemical assay and both instrumental spectrums, it was thought that the active compounds of fraction 4 and 5 were in the flavonoid group.